Reconsideration of urine culture for the diagnosis of acute pyelonephritis in children: a new challenging method for diagnosing acute pyelonephritis - Jun Ho Lee; Seonkyeong Rhie (Korean Pediatric Society, 2019)
Acute pyelonephritis (APN) should be detected and treated as soon as possible to reduce the risk of the development of acquired renal scarring. However, in the medical field, urine culture results are not available or considered when the prompt discrimination of APN is necessary and empirical treatment is started. Furthermore, urine culture cannot discriminate APN among children with febrile urinary tract infection (UTI) (pyelitis, lower UTI with other fever focus). Therefore, the usefulness of urine culture for diagnostic purposes is small and the sampling procedure is invasive. Congenital hypoplastic kidney is the most common cause of chronic kidney injury in children. Thus, it is desirable that a main target be detected as early as possible when imaging studies are performed in children with APN. However, if APN does not recur, no medical or surgical treatment or imaging studies would be needed because the acquired renal scar would not progress further. Therefore, the long-term prognosis of APN in young children, particularly infants, depends on the number of recurrent APN, not other febrile UTI. New methods that enable prompt, practical, and comfortable APN diagnosis in children are needed as alternatives to urinary catheterization for urine culture sampling.